2011
DOI: 10.1161/circulationaha.110.971622
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization and Functionality of Cardiac Progenitor Cells in Congenital Heart Patients

Abstract: Background Human cardiac progenitor cells (hCPCs) may promote myocardial regeneration in adult ischemic myocardium. The regenerative capacity of hCPCs in young patients with nonischemic congenital heart defects for potential use in congenital heart defect repair warrants exploration. Methods and Results Human right atrial specimens were obtained during routine congenital cardiac surgery across 3 groups: neonates (age, <30 days), infants (age, 1 month to 2 years), and children (age, >2 to ≤13 years). C-kit+ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
178
4
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(208 citation statements)
references
References 24 publications
(38 reference statements)
23
178
4
3
Order By: Relevance
“…It reported that the number of CSCs changed during postnatal maturation with the most abundance in neonatal period. Isolated cells had regenerative potential and they could be used as autologous cell sources for cell therapy of heart patients [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It reported that the number of CSCs changed during postnatal maturation with the most abundance in neonatal period. Isolated cells had regenerative potential and they could be used as autologous cell sources for cell therapy of heart patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…The candidate stem cell for transplantation must improve heart function without inducing an immune response, arrhythmias, or carcinogenesis [3]. Results of animal model studies and clinical trials suggest that transplantation of cardiac stem cells (CSCs), resident cardiac precursor cells in the heart, may be one of the best strategies to cure adult or pediatric heart diseases [4][5][6][7][8]. All CSCs populations contain most properties of stem cells: self-renewal, multi-lineage differentiation, and clonogenic potentials.…”
mentioning
confidence: 99%
“…A study by Scheubel et al also reported that aging inhibits endothelial progenitor cell mobilization in patients undergoing CABG [110]. Moreover, other researchers have suggested that aging is involved in mediating intrinsic characteristics of stem cells, such as cell growth, proliferation, differentiation, and senescence [77,[111][112][113][114]. Clearly, epidemiological studies show that heart diseases are more prevalent among the elderly population [115].…”
Section: Effect Of Age On Isolation and Function Of Cardiac Stem Cellsmentioning
confidence: 99%
“…91 c-Kit þ CPCs can be isolated from patients with various congenital heart defects, expanded in culture and differentiated towards the cardiomyogenic lineage. 92 Recently, it was reported that c-Kit þ stem cells promoted the formation of myocardium containing a network of blood vessels 20 days after injection into the infarction site of adult rats. 93 Similarly, intravascular delivery of c-Kit þ stem cells through the coronary arteries of rats has been shown to promote myocardial regeneration and reduce infarct size in a less invasive manner compared with surgical procedures.…”
Section: Directing Stem Cell Differentiation Into Cardiac Lineagementioning
confidence: 99%